Mucocele: Clinical Characteristics and Outcomes in 46 Operated Patients - Plantier,Diogo Barreto (2019)
Abstract Introduction Paranasal sinus mucocele is a benign, expansive lesion associated with paranasal sinus obstruction. It affectsmostly adults, and ismost common in the frontal and ethmoidal sinuses. Objective To evaluate outcomes in patients undergoing surgical treatment for paranasal sinus mucocele. Methods Retrospective review of medical records of patients treated for paranasal sinus mucocele at the ENT department of a tertiary care hospital between 2005 and 2016. Results Forty-six patients underwent surgical treatment of paranasal sinusmucocele. Themean age was 50.1 years, and 56.5% were male. The most prevalent symptom was pain, and the frontal sinus was most commonly affected. The vast majority of patients (89.1%) underwent endoscopic sinusmarsupialization; 10.9% required combined open and endoscopic access. Seven recurrences occurred. Conclusion Sinus mucocele is an expansive disease that primarily affects the frontal sinus of adult patients. In most cases, endoscopic surgery is an effective treatment modality.